Penetapan Wali Terhadap Anak Hasil Nikah Hamil di KUA Kledung: Analisis Maqashid Asy-Syari’ah - Rohiq, M.; Rofiq, Abdul; Mahargiani Rokhma, Eka (El-Qenon: Journal of Islamic Law, 2024)
Marriage is a sunnatullah (natural law) prescribed for humans to fulfill biological needs and clarify lineage. A legitimate marriage results in children who have a recognized legal status. On the other hand, an illegitimate marriage results in children who have the status of out-of-wedlock children, whose civil rights follow the mother and her family. In a legitimate marriage, one of the essential requirements is the presence of a guardian; a marriage without a guardian is invalid. According to Islamic jurisprudence, a legitimate child is one born at least six months after marriage or within the waiting period (iddah) of four months and ten days after the marriage ends. This paper aims to understand how marriage guardianship is determined for children born from marriages that occurred after pregnancy in Kledung Religious Affairs Office (KUA) and to analyze the legal basis considered in determining the marriage guardian for children born from marriages following pregnancy in Kledung KUA. If a child is born from a marriage that took place less than six months after the marriage, the parents’ marriage certificate is examined and compared with the birth certificate of the prospective bride. If it is proven that the prospective bride was born in less than six months, the guardian is automatically designated as the state-appointed guardian (wali hakim). If the child wants to marry and their father cannot serve as the marriage guardian, the guardian will be designated as the state-appointed guardian. This designation is in accordance with the principles of Shari’ah, which aim (maqashid) to protect lineage. Therefore, the view from the perspective of maqashid Shari’ah is considered to provide significant benefits (maslahah) to the Muslim community.